Sanctioned medical acts in the operating room - Markowski, Theresa (Operating Room Nurses Association of Canada Journal, 1989)
Operating room nursing has become a highly technical area requiring special training and education. Once this preparation has been achieved, on—going instruction is necessary in order to maintain the required levels of knowledge, skill and judgement.